MRPL13 Promotes Tumor Cell Proliferation, Migration and EMT Process in Breast Cancer Through the PI3K-AKT-mTOR Pathway - Cai M; Li H; Chen R; Zhou X (Cancer Management and Research, 2021)
Miaomiao Cai,1 Hanning Li,2 Runfa Chen,1 Xiang Zhou1 1College of Life Sciences and Health, Wuhan University of Science and Technology, Wuhan, Hubei, 430065, People’s Republic of China; 2Department of Thyroid and Breast Surgery, Tongji Hospital, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, 430030, People’s Republic of ChinaCorrespondence: Xiang ZhouCollege of Life Sciences and Health, Wuhan University of Science and Technology, Wuhan, Hubei, 430065, People’s Republic of ChinaTel +13699206313Email zhouxiang@wust.edu.cnPurpose: Breast cancer (BC), with varying histopathology, biology and response to systemic treatment, is the second leading cause of cancer-related mortality. Previous studies have inferred that the expression of mitochondrial ribosomal proteins (MRPs) is possibly related to the occurrence/progression of BC. MRPL13 might be one of the potential MRP candidates that are involved in BC tumorigenesis, but its role in BC has rarely been reported. The purpose of the current study was to evaluate the prognostic significance of MRPL13, as well as to explore its potential biological functions in BC.Materials and Methods: A series of bioinformatic and statistical methods were adopted to assess the MRPL13 expression profile, its relationship with clinicopathological characteristics, copy number variation (CNV), impact on clinical outcomes and relevant functions. All the results are analysed by 1097 BC patients collected from The Cancer Genome Atlas (TCGA) dataset and 52 clinical samples for immunohistochemistry (IHC) assay.Results: The results demonstrated that the expression of MRPL13 in BC tissues was remarkably elevated than that in normal breast tissues. In addition, the Kaplan-Meier curves and Cox model indicated that patients with high MRPL13 expression were connected to a worse prognosis, heralding the independent prognostic value of this protein in BC. Moreover, an enrichment analysis showed that MRPL13 was mainly involved in cell cycle/division-related, RNA processing (degradation/splicing), MYC targets and the MTORC1 pathways. In addition, RNA interference (RNAi)-mediated MRPL13 silencing remarkedly inhibited proliferation and migration as well as the expression of EMT-related genes of BC cells in vitro. Mechanistically, attenuation of MRPL13 significantly suppressed the phosphorylation of AKT and mTOR, which could be partially abolished by 740Y-P (a PI3K agonist).Conclusion: Our results provide evidence for the first time that increased MRPL13 expression correlates with adverse clinicopathological variables and unfavorable clinical outcomes of BC patients. Knockdown of MRPL13 restrains the proliferation and migration potential and EMT process of BC through inhibiting PI3K/AKT/mTOR signaling pathway.Keywords: breast cancer, MRPL13, prognosis, biomarker, PI3K-AKT-mTOR